Solidifying the White Domination through Racism and Slavery in Toni Morrison’s Beloved - Thohiriyah, Thohiriyah (Language Circle: Journal of Language and Literature, 2019)
Beloved is a novel written by American author, Toni Morrison. Through Beloved, Toni Morrison successfully depicts a heartbreaking phenomenon of slavery that happened in the USA in 1873. Morrison describes the phenomenon of dominance-submission interrelation patterns in a master-slave relationship. By using the concept of racism and slavery, the paper aims at scrutinizing how the whites perform racism and slavery to solidify their domination over the blacks. Besides, it is aimed at investigating the impacts of slavery and racism done by the whites which are experienced by the slaves. Library research and close-reading methods are employed to analyze the novel. Besides, the qualitative and contextual method which focuses on intrinsic and extrinsic elements is utilized. The result of the analysis shows that racism and slavery are major elements that solidify whites’ domination over black slaves. In other respect, racism and slavery lead to great negative impacts for the black slaves. Excessive trauma and identity loss are the major impacts experienced by the slaves as the consequence of slavery and racism.